2017
DOI: 10.23880/hij-16000101
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Leukaemia in Zimbabwe: A Ten Year Retrospective Study

Abstract: Background: Haematological malignancies are defined as primary cancers of blood cells. Leukaemia constitutes more than fifty-five percent of haematological malignancies. The epidemiology of leukaemia in Zimbabwe is currently unknown. Aim: To investigate the incidence of leukaemia in Zimbabwe during a ten year period from 2004 to 2013. Objective: To understand the latest epidemiology of leukaemia in the country in order to effectively manage the disease and inform policy makers. Methods: A ten year cross sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
0
1
Order By: Relevance
“…Sixty percent of the patients in this study were male, which is similar to other studies that have reported male predominance of acute leukemia. 14 - 16 Interestingly, females were more likely to die from acute leukemia, which is unlike previous studies that suggest that in adults, males have worse survival from both acute leukemia 17 and other cancers, 18 the reasons for which finding are yet to be investigated.…”
Section: Discussioncontrasting
confidence: 74%
“…Sixty percent of the patients in this study were male, which is similar to other studies that have reported male predominance of acute leukemia. 14 - 16 Interestingly, females were more likely to die from acute leukemia, which is unlike previous studies that suggest that in adults, males have worse survival from both acute leukemia 17 and other cancers, 18 the reasons for which finding are yet to be investigated.…”
Section: Discussioncontrasting
confidence: 74%